الأورام الليفية في الأمعاء الدقيقة – حالة نادرة لورم ليفي داخل البطن - مرتضى, ايمن (Latakia University Journal -Medical Sciences Series, 2018)
Back ground and purpose :desmoid tumors are infrequent cases ,with a large clinical variability ,location on abdominal wall ,mesentery and extra abdominal soft tissue. Histologically : benign tumors, but locally aggressive, they have a marked tendency to recurrence .there are two known variants: sporadic and associated to familial adenomatous polyposis ,its etiology remains unknown , but it appears to be related to estrogenic stimulation ,surgical aggression and mutation of chromosome 5. Diagnosis is usually difficult , and must combine medical history, semiology and imaging ,though only histological analysis of the specimen will provide a definitive diagnosis after surgical resection . Case report :male patient 64 years old, good general state ,chef complaint lower abdomen heaviness sensation , polyuria ,no digestive complaint, no medical and surgical antecedents . Physical examination shows palpation of giant mass in lower part of abdomen . CT abdomen with contrast :giant heterogeneous pelvic mass (17*15 cm) with clear limits . Surgical treatment : laparotomy (midline supra and infra umbilical incision ,resection of giant mass on account of ileum loop and her mesentery ,end to end anastomosis procedure ). Anatomopathology study :conformation of fibromatosis( desmoid tumors) by inmunohistochemical staining . Discussion :oligosymptomatic abdominal mass with respect the mucosa f the gastrointestinal tract lead clinical suspicion to mesenchymal tumors such as sarcomas, desmoid ,or GIST ز.Radiology testes are useful to confirm resectability and detected complications. Treatment with chemotherapy and / or radiotherapy should be considered in unrespectable disease . Diagnosis is confirmed after histological and inmunohistochemical analysis of the specimen ,which in cases of a desmoid will show negative expression to markers of sarcoma (actin,desmin,S100) or GIST (CD117,DOG1,PDGFRA ) ,and positive staining with anti-beta-catenin . Conclusion :desmoid tumors should be considered in the differential diagnosis of abdominal oligosymptomatic masses ,especially in fertile women or if history of surgical trauma. Patient with desmoid tumors should undergo colonic polyposis screening ,as well as patients with adenomatous polyposis and an abdominal mass should lead suspected diagnosis to the possibility of a desmoid tumor . الأهمية والغاية من البحث:تعتبر الأورام الليفية (desmoid tumors) من الحالات غير الشائعة, مع تنوعها السريري الواسع, بالإضافة لتوضعها في أماكن مختلفة (جدار البطن, المساريقا والأمعاء, والأنسجة الرخوة خارج البطن). تعتبر سليمة نسيجياً ولكنها غازية موضعيا ولها ميل واضح للنكس. هناك نوعان: فردية, ومترافقة مع البو ليبات الغدية العائلية. تبقى الاسباب غير معروفة ولكنها تبدو متعلقة بالحادثات الاستروجينية, والرض الجراحي والطفرة في الصبغي 5. التشخيص عادة صعب ويجب ترافق القصة السريرية مع الأعراض والدراسة الشعاعية. التشريح المرضي للعينة المستأصلة فقط من يعطي التشخيص النهائي. تقرير الحالة:مريض ذكر 64 سنة, حالة عامة جيدة. الشكوى الرئيسية حس ثقل وانتفاخ في البطن مع تعدد بيلات, لا توجد شكاية هضمية كما لا توجد سوابق مرضية أو جراحية. أظهر التصوير الطبقي المحوري للبطن كتلة كبيرة تقيس (15*17) سم غير متجانسة ذات توضع حوضي وحدود واضحة. أجري فتح بطن على الخط الناصف واستئصال لكتلة كبيرة على حساب عروة دقاقية مع مساريقاها ومن ثم اجراء مفاغره نهائية نهائية. التشريح المرضي أكد تشخيص الورم الليفي (fibromatosis –desmoid tumors) بعد اجراء التلوين المناعي. المناقشة:يقود التشخيص التفريقي للكتل البطنية قليلة الأعراض والتي تحترم مخاطية السبيل الهضمي الى الشك سريريا بالأورام الميزانشيمية مثل الساركوما, الأورام الليفية, أو أورام اللحمة المعوية المعدية, الدراسة الشعاعية مهمة لتحديد امكانية الاستئصال وتوقع المضاعفات .نلجأ للعلاج الكيماوي و/أو الشعاعي عند عدم امكانية الاستئصال. الدراسة النسيجية والتلوين المناعي للعينة يضع التشخيص, حيث نلاحظ في الأورام الليفية سلبية واسمات الساركوما (actin,desmin,s100), وسلبية واسمات أورام اللحمة المعدية المعوية (CD117,DOG1,PDGFRA), وايجابية الواسمات (anti – beta – catenin ,Vimentin, ) النتيجة: يجب أخذ الأورام الليفية كأحد التشاخيص التفريقية للكتل البطنية قليلة الأعراض خاصة عند النساء في سن الانجاب أو وجود قصة لرض جراحي, يجب البحث عن بوليبات القولون عند مرضى الأورام الليفية, بالمقابل يجب الشك بالأورام الليفية عند وجود كتلة بطن لمريض لديه بوليبات غدية.